Developing Customer Satisfaction Strategies for Oke Jek Tebing Tinggi Online Transportation Users during COVID-19 - Sagala, Yomeini Margareth; Islamiarti, Dian (Indonesia Academia Research Society, 2024)
This study investigated the optimal development strategy for Oke Jek, an online transportation service in Tebing Tinggi, to enhance customer satisfaction during the COVID-19 pandemic. Oke Jek, which commenced operations in 2019, faces unique challenges in maintaining customer satisfaction while prioritizing safety and user experience. The research employed a qualitative approach, utilizing primary and secondary data collected through interviews, observations, and documentation from seven respondents. The theoretical framework is supported by development, marketing, and customer satisfaction theories. This study utilizes SWOT analysis to examine the internal (IFE) and external (EFE) environments. The IFE matrix, which evaluates strengths and weaknesses, yielded a score of 1.45, while the EFE matrix, which assesses opportunities and threats, produced a score of 1.15. These results position Oke Jek in Quadrant I, indicating an Aggressive Strategy as the most appropriate approach. On the basis of SWOT analysis, four alternative strategies were identified: Strengths-Opportunities (SO), Weaknesses-Opportunities (WO), Strengths-Threats (ST), and Weaknesses-Threats (WT). The findings suggest that, to enhance customer satisfaction, Oke Jek should implement a comprehensive strategy focusing on safety measures, effective communication of health protocols, and improved application functionality for streamlined bookings and payments. This approach aimed to address the unique challenges posed by the COVID-19 pandemic while maintaining a competitive advantage in the online transportation market.